Circadian-Hypoxia Link and its Potential for Treatment of Cardiovascular Disease - Bartman, Colleen Marie (Curr Pharm Des, 2019)
Throughout evolutionary time, all organisms and species on Earth evolved with an adaptation to consistent oscillations of sunlight and darkness, now recognized as ‘circadian rhythm.’ Single-cellular to multi-system organisms use circadian biology to synchronize to the external environment and provide predictive adaptation to changes in cellular homeostasis. Dysregulation of circadian biology has been implicated in numerous prevalent human diseases, and subsequently targeting the circadian machinery may provide innovative preventative or treatment strategies. Discovery of ‘peripheral circadian clocks’ unleashed widespread investigations into the potential roles of clock biology in cellular, tissue, and organ function in healthy and diseased states. Particularly, oxygen-sensing pathways (e.g. hypoxia inducible factor, HIF1), are critical for adaptation to changes in oxygen availability in diseases such as myocardial ischemia. Recent investigations have identified a connection between the circadian rhythm protein Period 2 (PER2) and HIF1A that may elucidate an evolutionarily conserved cellular network that can be targeted to manipulate metabolic function in stressed conditions like hypoxia or ischemia. Understanding the link between circadian and hypoxia pathways may provide insights and subsequent innovative therapeutic strategies for patients with myocardial ischemia. This review addresses our current understanding of the connection between light-sensing pathways (PER2), and oxygen-sensing pathways (HIF1A), in the context of myocardial ischemia and lays the groundwork for future studies to take advantage of these two evolutionarily conserved pathways in the treatment of myocardial ischemia.